Food and feeding habits of freshwater cypnnid, Amblypharyngodon mola (Ham.) - Pishka, Ravi Shankar; Swamy, B Rama; Devi, P Indira (Indian Journal of Fisheries, 2011)
Amblypharyngodon mola (Ham.), a herbivorous bottm feeder, feeds on algae, diatoms and higher aquatic plants. Different food items in relation to size, seasonal variation and intensity of feeding were investigated in this fish.